2020
DOI: 10.1093/cid/ciaa677
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ACE Inhibitor/ARB Use Is Associated With Severe Renal Dysfunction and Acute Kidney Injury in Patients With Severe COVID-19: Results From a Referral Center Cohort in the Northeast of France

Abstract: Abstract Background In patients with severe coronavirus disease 2019 (COVID-19), data are scarce and conflicting regarding whether chronic use of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) influences disease outcomes. In patients with severe COVID-19, we assessed the association between chronic ACEI/ARB use and the occurrence of kidney, lung, heart, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 37 publications
(51 reference statements)
2
57
2
Order By: Relevance
“…Some studies did not find any relationship between the use of ACE-I or ARB and the development of AKI 31,32 . Contrary to these results, Oussalah et al reported a harmful effect of long-term ACE-I or ARB use on the renal function and further interaction with the occurrence of AKI and ARDS in 149 patients with severe COVID-19 33 . Our study highlighted the possible association between ACE-I or ARB use and a significant increase in both ARDS and AKI.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies did not find any relationship between the use of ACE-I or ARB and the development of AKI 31,32 . Contrary to these results, Oussalah et al reported a harmful effect of long-term ACE-I or ARB use on the renal function and further interaction with the occurrence of AKI and ARDS in 149 patients with severe COVID-19 33 . Our study highlighted the possible association between ACE-I or ARB use and a significant increase in both ARDS and AKI.…”
Section: Discussionmentioning
confidence: 82%
“…The evidence for the safety of other ACE2-raising drugs, used alone or in combination, is sparse but the majority of the studies discussed herein suggested that these drugs are not associated with adverse outcomes with exception of one study indicating increased risk of AKI in patients receiving ACEI/ARBs in severe COVID-19 disease [117]. Although the majority of clinical studies examining outcomes on COVID-19 patients have reported results for combined use of ACEIs and ARBs, it should be noted that these two drug classes have divergent cardiovascular effects and outcomes in patients [152], and perhaps future studies should aim to report results for ACEIs and ARBs separately.…”
Section: Resultsmentioning
confidence: 95%
“…A large body of evidence from clinical observational studies reported thus far, as well as our recalculation of meta-analysis data on all-cause mortality, supports continued use of ACEIs/ARBs in COVID-19 patients. Although these drugs generally appear to be clinically safe, their chronic use in severe COVID-19 patients might increase the risk of acute renal injury [117]. Evidence also exists for the beneficial effects of ACEIs/ARBs in some sub-populations of COVID-19 patients such as in lowering risk of mortality in hypertensive patients or decreasing risk of hospitalisation for COVID-19 patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations